Young-Alpine alkali feldspar granites (alaskites) from Mt. Požeška Gora in Slavonia, northern Yugoslavia - Pamić, Jakob (Geologija, 1987)
The paper deals with geology, geochemistry and petrology of granites from Mt. Požeška Gora in Slavonia which have not been so far studied. Granites invade albite rhyolites and metabasalts which represent a part of Upper Cretaceous volcanic-sedimentary complex which is allochthonous (thrust?) over the surrounding Neogene sediments. The granites represent products of final stages of the same magmatic activity which produced the adjacent Upper Cretaceous albite rhyolites and metabasalts. Based on modal composition, granites belong to alkali feldspar varieties consisting mainly of quartz, albite, orthoclase, microperthite and myrmekitic intergrowth of quartz and albite whose Chemical composition is documented by microprobe analyses. The granites are extremely leucocratic so that they can be attributed to alaskites. According to petrochemical features granites are very similar to the adjacent albite rhyolites. The geotectonic setting of alkali feldspar granites of Mt. Požeška Gora cannot be reliably determined on the basis of standard geochemical discrimination diagrams. Based on certain geochemical and petrological characteristics, the granites can be correlated with A-type granites. Granite magmatism of Mt. Požeška Gora is considered as a part of complex geodynamic processes which took place at the end of the Upper Cretaceous within the structure of a presumed magmatic are whose relies can be recognized within the Prosara-Motajica-Cer- Bukulja zone of the northernmost Dinarides.